Differential pattern in labour use on male vs female managed farms and its economic consequences : a case study from Manipur, India - Laxmi Thingbaijam; A Ghosh; K K Das (Agricultural Economics Research Review, 2023)
Male domination in farming and farm management is slowly losing its hold world-wide, especially in the third world countries. In India, about one-fourth of the total farm households are managed by females. This paper examines the gender dimensions in agriculture utilizing data from a survey of 120 households distributed over two valley districts in Indian state of Manipur. Our findings indicate that there remains crop-specificity, operation-specificity and source-specificity in labour use by gender. Females are found to be dominant in non-traditional crops (e.g., tomato, mustard and peas). The female-managed households also hire more of females. Important operations like sowing, harvesting and weeding are mostly performed by female labourers and female-employers. Increased cropping intensity by bringing more and more non-cereal crops in the cropping system favours engagement of more female labourers which may be helpful both in crop diversification and in enhancing farm income. Farm mechanisation has a positive influence on female employment.